Mykhailo Verikivskyiʼs “Five Pieces For String Quartet on Folk Themes”: Principles of Folklore Processing - Derevianchenko, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of research. The introduction to the musicological using of the manuscript of M. Verikyvskyi's early work, which was previously only briefly mentioned in the literature, is connected with the current scientific trend of studying little-known pages of the history of Ukrainian music of the era of national liberation struggles of the 20th century. The return of the forgotten artefact of the composer's heritage is intended to contribute to the establishment of more complete and objective picture of the development of genres, stylistic trends, individual authorial style, etc. The purpose of the study. The purpose of the article is to explore the principles of processing folklore in the M. Verikyvskyʼs cycle "Five pieces for a string quartet on folk themes" in the genrestylistic aspect, to find out the extent of the influence of theoretical views and didactic instructions of B. Yavorskyi on the writing of the work, to outline the meaning of the composition in the context of the evolution of the author's creativity and directions development of Ukrainian quartet music of the 20th century. Methods. The article uses source, genre and style studies, structural and intonationalconstructive methods of analysis of musical work. The results and conclusions. The composer's notes in the margins of the manuscript are commented in the context of the artist's creative life (1921), social-political and aesthetic-artistic trends of the era, communication with the teacher of composition. The stylistic features of neofolklorism were revealed in the work: appeal to folk archaic and principles of folklore thinking, combination of folk elements with technical and compositional means of the modernist era, subjugation of the folklore theme to an individual artistic idea. The influence of the theoretical and didactic instructions of B. Yavorskyi, M. Verikyvskyiʼs teacher at the Kyiv Conservatory, can be observed on two levels: 1) general aesthetic views on the use of folklore in the composer's work, 2) specific compositional and stylistic techniques in the plane of lado-harmonic processes (the role of the tritone, constructive and modal continuous exposition), dynamization of the metrorhythm, texture, formation. In the composer's creativity, this work initiates the genre of instrumental folklore composition, prepares the appearance of large-scale neo-folkloric compositions (oratorio, symphonic uite, ballet, opera), tests for the first time the model of the five-part suite cycle, built on the principles of contrast, symmetry and concentricity. In Ukrainian quartet music, this opus is located near the origins of the folklore line of development of the genres of piece (folk miniature) and suite.